Enhanced (CuO/ZnO) Nanocomposites Synthesized via Thermal Evaporation for High-Performance Photodetector Applications - A. Jabber, Ahmed; R. Abdulridha, Ali (Journal of Neonatal Surgery, 2025)
In this article, thin films of copper oxide (CuO) doped with zinc oxide (ZnO) were produced using thermal evaporation at 1×10-7 bar pressure and 0.5 nm/s deposition rate. Deposition on glass substrates yielded a 50±0.2 nm film thickness at ambient temperature. After annealing at 400 0C for two hours, XRD examination revealed a monoclinic wurtzite structure of CuO. AFM investigation found a 54.46% increase in surface roughness, a 52.5% increase in RMS, and a 27.5% average particle size with increasing ZnO concentration. FE-SEM and EDX confirmed the uniform distribution of Cu, Zn, O, and CuO/ZnO nanocomposites. Higher ZnO improved absorption, refractive index, and extinction coefficient; energy band gap fell from 3.601 to 3.388 eV. Electrical studies showed enhanced DC conductivity, resistance, and activation energy with higher ZnO concentration and temperature. I–V tests showed greater photocurrent, responsiveness, and sensitivity, making these films promising for optoelectronic and photodetector applications.